Monetary intelligence and behavioral economics: The enron effect—love of money, corporate ethical values, corruption perceptions index (CPI), and dishonesty across 31 geopolitical entities - Tang, Thomas Li-Ping; Sutarso, Toto; Ansari, Mahfooz A.; Lim, Vivien Kim Geok; Teo, Thompson Sian Hin; Arias-Galicia, Fernando; Garber, Ilya E.; Chiu, Randy Ki Kwan; Charles-Pauvers, Brigitte; Luna-Arocas, Roberto; Vlerick, Peter; Akande, Adebowale Williams; et al. (Springer Netherlands, 2018)
Monetary intelligence theory asserts that individuals apply their money attitude to frame critical concerns in the context and strategically select certain options to achieve financial goals and ultimate happiness. This study explores the dark side of monetary Intelligence and behavioral economics—dishonesty (corruption). Dishonesty, a risky prospect, involves cost–benefit analysis of self-interest.We frame good or bad barrels in the environmental context as a proxy of high or low probability of getting caught for dishonesty, respectively. We theorize: The magnitude and intensity of the relationship between love of money and dishonest prospect (dishonesty) may reveal how individuals frame dishonesty in the context of two levels of subjective norm—perceived corporate ethical values at the micro-level (CEV, Level 1) and Corruption Perceptions Index at the macro-level (CPI, Level 2), collected from multiple sources. Based on 6382 managers in 31 geopolitical entities across six continents, our cross-level three-way interaction effect illustrates: As expected, managers in good barrels (high CEV/high CPI), mixed barrels (low CEV/high CPI or high CEV/low CPI), and bad barrels (low CEV/low CPI) display low, medium, and high magnitude of dishonesty, respectively. With high CEV, the intensity is the same across cultures. With low CEV, the intensity of dishonesty is the highest in high CPI entities (risk seeking of high probability)— the Enron Effect, but the lowest in low CPI entities (risk aversion of low probability). CPI has a strong impact on the magnitude of dishonesty, whereas CEV has a strong impact on the intensity of dishonesty. We demonstrate dishonesty in light of monetary values and two frames of social norm, revealing critical implications to the field of behavioral economics and business ethics.